MANAJEMEN PERSONIL PEMERINTAH DAERAH KEKINIAN DI INDONESIA - Irfan Ridwan Maksum (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2019)
Local government personnel management in Indonesia has, structurally and culturally, not changed fundamentally since the reform broke out at the end of 1990’s. Under the Law Number 22 Year 1999, articles number 7 and 75, the local government personnel system seemed to separate from the central personnel system. However, the local government did not seemed to be capableenough to carry-out their local systems. Finally, under Law Number 32 Year 2004, the condition remains more or less the same with ’pangreh-praja’ culture.